Recreational 3 × 3 basketball elicits higher heart rate, enjoyment, and physical activity intensities but lower blood lactate and perceived exertion compared to HIIT in active young adults - Daniele Conte; Inga Lukonaitiene; Kestutis Matulaitis; Audrius Snieckus; Audinga Kniubaite; Rasa Kreivyte; Sigitas Kamandulis (Termedia Publishing House, 2023)
This study aimed to assess and compare the physiological [percentage of maximal heart rate (%HR max ), blood lactate (BLa), creatine kinase (CK)], hormonal (testosterone, cortisol), psychological [rating of perceived exertion (RPE), enjoyment] and physical [percentage of moderate-to-vigorous physical activity (%MVPA) and vigorous activity (%VA)] responses of recreational 3×3 basketball (3×3BB) and high-intensity interval training (HIIT) in active young adults. Twelve apparently healthy male recreational basketball players (age: 23±3 years; body mass: 82±15 kg; stature: 188±15 cm) completed a 3×3BB match and HIIT with similar duration. %HR max , %MVPA and %VA were monitored during the protocols, while BLa, cortisol, and testosterone were measured before and after each protocol. CK was measured before the protocols and at 24 h, while RPE and enjoyment were assessed at the end of each protocol. 3×3BB elicited higher %HR max (p < 0.001; d = -1.6, large), %MVPA (p < 0.001; d = 2.7, very large), %VA (p = 0.030; d = 0.8, moderate), enjoyment (p = 0.014; r-value = -0.500, large), and lower RPE (p = 0.024; r-value = -0.462, moderate) compared to the HIIT condition. Moreover, higher values of BLa were found in HIIT compared to 3×3BB at post-condition (p = 0.020; r-value = -0.601, large), while CK analysis showed only an increase within the HIIT condition (p = 0.020; r-value = -0.599, large). A time effect was found for both testosterone (p < 0.001, η 2 p = 0.526, moderate) and cortisol (p = 0.005, η 2 p = 0.743, strong), while no between-condition effect or interaction was found (p > 0.05). 3×3BB elicits higher %HR max , enjoyment, and physical activity intensities but lower BLa and RPE compared to HIIT in active young adults and might be considered as a potentially suitable activity to increase participants' health status.